Post-lingual non-syndromic hearing loss phenotype: a polygenic case with 2 biallelic mutations in MYO15A and MITF - Athar Khalil; Samer Bou Karroum; Rana Barake; Gabriel Dunya; Samer Abou-Rizk; Amina Kamar; Georges Nemer; Marc Bassim (BMC, 2020)
Abstract Background Hearing loss (HL) represents the most common congenital sensory impairment with an incidence of 1-5 per 1000 live births. Non-syndromic hearing loss (NSHL) is an isolated finding that is not part of any other disorder accounting for 70% of all genetic hearing loss cases. Methods In the current study, we reported a polygenic mode of inheritance in an NSHL consanguineous family using exome sequencing technology and we evaluated the possible effect of the detected single nucleotide variants (SNVs) using in silico methods. Results Two bi-allelic SNVs were detected in the affected patients; a MYO15A (. p.V485A) variant, and a novel MITF (p.P338L) variant. Along with these homozygous mutations, we detected two heterozygous variants in well described hearing loss genes (MYO7A and MYH14). The novel MITF p. Pro338Leu missense mutation was predicted to change the protein structure and function. Conclusion A novel MITF mutation along with a previously described MYO15A mutation segregate with an autosomal recessive non-syndromic HL case with a post-lingual onset. The findings highlight the importance of carrying whole exome sequencing for a comprehensive assessment of HL genetic heterogeneity.